Pterygodermatites (Paucipectines) andyraicola n. sp. (Spirurida: Rictulariidae), an intestinal nematode of neotropical molossidae bats from Brazil - Cardia, Daniel F. F.; Tebaldi, José H. [UNESP]; Fornazari, Felipe [UNESP]; Menozzi, Benedito D. [UNESP]; Langoni, Helio [UNESP]; Nascimento, Adjair A. [UNESP]; Bresciani, Katia D. S. [UNESP]; Lux Hoppe, Estevam G. [UNESP] (Helminthological Society, 2015)
A new nematode species, Pterygodermatites (Paucipectines) andyraicola n. sp., is described from the small intestine of 4 neotropical species of Molossidae bats captured in São Paulo State, Brazil. The newly recognized species is characterized by the presence of a subterminal hexagonal oral opening with 24 triangular and prominent denticles of the same shape and size and a buccal capsule with 3 oesophageal teeth with jagged edges. The male has a robust body covered with 40 to 43 pairs of subventral cuticular spines, a coiled tail with thin caudal alae, 10 pairs of papillae, and a single, precloacal, semicircular cuticular fan on the ventral surface. The first pair of precloacal papillae are composed of 2 short pedunculated papillae, a feature that seems to be unique to P. (P.) andyraicola when compared to other species of the subgenus Pterygodermatites (Paucipectines). Equal spicules and the cone-shaped gubernaculum poorly sclerotized. The female has a robust body, thinner in the anterior portion, covered by 2 rows of 67 to 80 cuticular spines, of which the first 41 to 43 pairs are anterior to the vulvar opening and symmetrically arranged, which is in contrast to the asymmetrical disposition of the postvulvar spines. This is the 15th species in the genus described from mammals in the Neotropical ecozone and the third parasitizing bats in this biogeographic region.
Keywords: Chiroptera; helminth; morphology; Nematoda; parasite; taxonomy